Factors Related to Nurse Job Satisfaction at Aisyiyah Siti Fatimah Tulangan Hospital - M. Arwani (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
The purpose of this study was to determine the factors associated with job satisfaction of nurses in the inpatient room of Aisyiyah Siti Fatimah Hospital. The research design used was cross sectional to determine the relationship between certain factors and nurse job satisfaction. After being analyzed with the chi square test using the SPSS-15 program, the results obtained were compensation related to the job satisfaction of nurses in the inpatient room of Aisyiyah Siti Fatimah Tulangan Hospital with a p value = 0.001, conditions and work groups related to job satisfaction of nurses in the work room. inpatient care at Aisyiyah Siti Fatimah Reinforcement Hospital with a p value = 0.002, and Supervisor is related to nurse job satisfaction in the inpatient room of Aisyiyah Siti Fatimah Reinforcement Hospital with a p = 0.002. hospitals need to pay attention to policies that accommodate all parties in the context of providing compensation, pay attention to conditions and work groups, and the leadership of the head of the room needs to be maintained and improved so that nurse job satisfaction in the hospital increases.